On element-connectivity preserving graph simplification - Chandra Chekuri (2018)
© Springer-Verlag Berlin Heidelberg 2015. The notion of element-connectivity has found several important applications in network design and routing problems. We focus on a reduction step that preserves the element-connectivity [18,4,3], which when applied repeatedly allows one to reduce the original graph to a simpler one. This pre-processing step is a crucial ingredient in several applications. In this paper we revisit this reduction step and provide a new proof via the use of setpairs. Our main contribution is algorithmic results for several basic problems on element-connectivity including the problem of achieving the aforementioned graph simplification.We utilize the underlying submodularity properties of element-connectivity to derive faster algorithms.